Herpes simplex virus type 1 latency-associated transcript (LAT) promoter deletion mutants can express a 2-kilobase transcript mapping to the LAT region. - Nicosia, M (1993)
The results of studies in several laboratories suggest that a TATA box-containing promoter located in the herpes simplex virus type 1 internal long repeat and long terminal repeat elements drives expression of the latency-associated transcripts (LATs). In the present study, we show that expression of a 2-kb LAT-related transcript can occur in the absence of this LAT TATA promoter, indicating the existence of a cryptic promoter. By Northern (RNA) blot analysis, we have examined LAT expression by herpes simplex virus type 1 variant strains KOS/29 and 1704, which contain deletions of the LAT promoter region. Our data indicate that KOS/29, despite lacking the 203-bp fragment which contains the LAT TATA box, can express a 2-kb LAT-related transcript during productive infection in tissue culture and in mouse trigeminal ganglia during acute infection and reactivation. Similarly, strain 1704, which contains a larger deletion in this promoter region, also expresses a 2-kb LAT-related transcript during tissue culture infection and reactivation of latently infected trigeminal ganglia. However, LATs are not expressed with either virus during latency. Northern blot analysis with a single-stranded, oligonucleotide probe demonstrates that the 2-kb LAT and LAT-related transcript are colinear and share a large area of sequence similarity. These findings suggest the existence of a second promoter in the LAT gene which can function during lytic infection and reactivation, at least in the absence of the LAT TATA promoter. We propose that this cryptic promoter is located either in a proximal region approximately 300 bp upstream of the start site of the 2-kb LAT or in a distal region starting over 1,226 bp upstream of this site.